Selected properties of phosphorus dendrimers: green approaches to catalysis - Caminade, Anne-Marie; Maraval, Valérie (Comptes Rendus. Chimie, 2024)
This review describes the synthesis of polyphosphorhydrazone (PPH) dendrimers, which are highly branched macromolecules, having a phosphorus atom at each branching point. The properties of these PPH dendrimers in the field of catalysis are then described. The review is organized to illustrate in the first part how the specificities of dendrimers could contribute to green chemistry. This concerns in particular the dendritic effect that is an increased efficiency (yield, enantioselectivity, etc.) when the size of the dendrimer increases, the recovery and reuse of the dendritic catalyst, the decreased leaching, and the entrapping of nanoparticles. In a second part, some even greener approaches of catalysis with dendrimers will be displayed, such as catalysis in water, switchable catalysis, and organocatalysis (no metal used). Different types of catalytic reactions have been studied, such as Stille, Suzuki and Sonogashira couplings, Knoevenagel condensations, Michael additions, asymmetric allylic alkylations, O- and N-arylation and vinylation reactions, [2${+}$2${+}$2]-cycloaddition reactions, isomerization of 1-octan-3-ol, Friedel–Crafts acylations, Heck reactions, hydrogenations, hydrations, transfer hydrogenations, amination of $β $-dicarbonyl compounds, etc.